Methodology of calculating required chloride diffusion coefficient for intended service life as function of concrete cover in reinforced marine structures. (October 2016) - Justnes, H.; Kim, M.O.; Ng, S.; Qian, X.
Abstract: For marine reinforced concrete (RC) structures, chloride initiated corrosion of reinforcement is generally accepted as the service life limiting degradation mechanism. A methodology is described for how the maximum required chloride diffusion coefficient (D) of a concrete for achieving an intended service life (t) can simply be calculated as a function of concrete cover thickness (x) over the reinforcement by D = constant·x 2 /t. The principle is based on the usual mathematical solution to Fick's 2nd law of diffusion. The constant is broken down into 3 factors; chloride concentration factor, aging factor and temperature factor, in which input parameters have to be selected. These factors are calculated for a range of selected input parameters illustrating their sensitivity. The largest uncertainty lays in proper selection of the aging factor of the diffusion coefficient. Some concrete recipes satisfying estimated chloride diffusion coefficients are proposed as part of the methodology.